Less cheating? The effects of prefilled forms on compliance behavior - Martin Fochmann; Nadja Müller; Michael Overesch (Arbeitskreis Quantitative Steuerlehre (arqus), 2018)
As a consequence of the digital transformation, individuals are often confronted with prefilled forms or prefilled data entry masks. In situations where cheating and lying are of concern, prefilling and defaults might reduce dishonest behavior. In a controlled experiment, we investigate how correctly and incorrectly prefilled forms influence compliance behavior. We frame our experiment as filing the annual income tax return. We show that correct prefilling enhances compliance. However, in cases of incorrect prefilling, we observe asymmetric effects. If prefilled income is lower than true income, we find no positive compliance effect, and compliance is on the same level as with blank forms. If prefilled income is higher than true income, prefilling still has a positive effect on compliance. In that case, compliance is on the same level as with correctly prefilled forms and higher than with blank forms. Our study contributes to the literature on cheating and lying by showing that prefilled forms and defaults affect compliance by changing the moral costs of dishonest behavior.
Keywords: C91; D14; H26; 330; Dishonesty; Defaults; Prefilled Forms; Tax Compliance; Behavioral Economics